Genetically decreased CYP2A6 and the risk of tobacco dependence: a prospective study of novice smokers. Issue 4 (24th November 2004) - O'Loughlin, J; Paradis, G; Kim, W; DiFranza, J; Meshefedjian, G; McMillan-Davey, E; Wong, S; Hanley, J; Tyndale, R F
Abstract : Objective: Case control studies in adults suggest that defective alleles in the gene that codes for the hepatic cytochrome P450 2A6 ( CYP2A6 ) protect against nicotine dependence (ND) and higher levels of cigarette consumption. These two hypotheses were tested in young adolescents. Design: Self reports of tobacco use and ND symptoms were collected every 3–4 months in a prospective study of 1293 grade 7 students from a convenience sample of 10 schools. Subjects: 281 smokers with genetic data were analysed; those who were not already tobacco dependent and who had inhaled (n = 228) were followed 29.9 months on average, until they became dependent or were censored. Main outcome measures: The association between metabolic activity, represented by CYP2A6 genotype, and conversion to dependence was analysed using Cox's proportional hazards model. Results: During follow up 67 subjects (29.4%) became dependent. Relative to CYP2A6*1/*1, having 1–2 copies of the inactive CYP2A6*2 or *4 variant was a strong risk factor for developing dependence (hazard ratio 2.8, 95% confidence 1.3 to 6.3). Subjects with 1–2 partially inactive CYP2A6*9 or *12 variants were not at increased risk. Mean past-week cigarette consumption at the end of follow up (controlling for age, sex, and number of months since first inhalation) among dependent subjects was 29.1 among normal inactivators, compared to 17.2, and 12.7 among slower (1–2 copies of * 9 or * 12 ), and slowest (1–2 copies of *2 or *4 ) inactivators, respectively (p = 0.09). Conclusion: Adolescents with 1–2 copies of CYP2A6*2 or * 4 are at substantially increased risk of becoming dependent but smoke less once dependent. Genetic risk for ND may need to be considered in the conceptualisation of tobacco control programmes for adolescents.